Inefficient fire-sales in decentralized asset markets - Ehsan Ebrahimy (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2019)
It is challenging to explain the collapse in the price of subprime mortgage-backed securities (MBS) during the Financial Crisis of 2008, using the existing models of fire-sale. I present amodel to demonstrate that fire-sales may happen evenwhen there is a relatively sizable pool of natural buyers and in the absence of asymmetric information, due to a coordination failure among buyers: buyers' waiting to trade at a lower price tomorrow, can lead to a collapse in the price and trade volume today. In particular, I show that when trade is decentralized and participation is endogenous, a medium level of asset demand and liquidity needs that are expected to increase over time create complementarity among buyers' decisions to wait. This complementarity makes competitive markets prone to coordination failures and fire-sales accompanied by a collapse in the trade volume. Fire-sales may also be inefficient. I also discuss various policy options to eliminate the risk of fire-sales in such a setup.
Keywords: G01; G12; D61; D62; D83; E44; 330; fire-sales; coordination failure; decentralized markets; competitive search